Pandemie als Strafe Gottes? Das Alte Testament als angeblicher Kronzeuge einer populären Leiddeutung - Seidl, Theodor (Münchener theologische Zeitschrift, 2020)
The principle of divine retaliation of human sin is present in many texts of the OT. But it is part of its concepts which are dependent on historical and cultural circumstances of the Ancient Near East. Critical voices against a mechanical application of the principle exist already in special wisdom and prophetic literature of OT. The article discusses five textual examples using this principle as background. But they have different main intentions and are therefore unsuitable to interpret the present pandemic as divine retaliation. (English)